1990
DOI: 10.1038/bjc.1990.29
|View full text |Cite|
|
Sign up to set email alerts
|

Serum oestradiol in women with and without breast disease

Abstract: Summary It has been suggested that the percentage of non-protein-bound or free oestradiol (E2) is abnormally high in patients with breast cancer. In this study, the serum oestradiol profiles of a large group of women were analysed to determine whether a significant correlation could be found between serum oestradiol and various breast diseases. In addition oestradiol levels were measured in relation to sex hormone binding globulin (SHBG), albumin levels, oestrogen receptor status and family history of breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Prior studies have not shown strong or significant differences in levels of estrogens (6-10), androgens (9, 11), or sex hormone binding globulin (6)(7)(8)(9) in postmenopausal patients with and without benign breast disease. Most of the published studies have been based on small sample sizes (6, 9, 10), did not distinguish between proliferative and nonproliferative changes (7,8), and did not include a rigorous pathology review (6)(7)(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have not shown strong or significant differences in levels of estrogens (6-10), androgens (9, 11), or sex hormone binding globulin (6)(7)(8)(9) in postmenopausal patients with and without benign breast disease. Most of the published studies have been based on small sample sizes (6, 9, 10), did not distinguish between proliferative and nonproliferative changes (7,8), and did not include a rigorous pathology review (6)(7)(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the published studies have been based on small sample sizes (6, 9, 10), did not distinguish between proliferative and nonproliferative changes (7,8), and did not include a rigorous pathology review (6)(7)(8)(9)(10). All of these studies were done at a time when endogenous hormone assays were notably less reliable and accurate than they are now.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperplasia of mammary gland (HMG) is a pathologic hyperplasia of the mammary gland lobules induced by an imbalance of estrogen and progesterone [1]. It is related to menstrual cycle, lactation, occupation, sex hormone use, diet, and stress [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperplasia of mammary gland (HMG) is a kind of pathological hyperplasia of the lobules of the mammary gland induced by balance disorder of estrogen and progesterone [1]. HMG is related to occupation, abuse of sex hormone drugs, diet and mental pressure [2,3].…”
Section: Introductionmentioning
confidence: 99%